Investigation of sustainable high-β scenarios in the JT-60SA C-wall. (2nd August 2017) - Romanelli, M.; Aresta-Belo, P.; Corrigan, G.; Garzotti, L.; Harting, D.; Koechl, F.; Saarelma, S.; Wiesen, S.; Wischmeier, M.; Zagórski, R.; Bolzonella, T.; Pigatto, L.; et al.
Abstract: One of the main goals of the JT-60SA C-wall is the study of steady-state plasma scenarios characterised by high fractions of bootstrap current, low flux consumption and sustainable divertor heat-loads (advanced scenarios). The feasibility of the above scenarios will depend on the demonstration of simultaneous control of core/SOL/divertor conditions to achieve large core pressure/pressure gradients, and preventing impurity accumulation while ensuring an acceptable power load on the divertor targets. In this paper two scenarios at 2.3 MA, 1.7 T with 30 MW and 17 MW of NBI heating, respectively, and 7 MW of ECRH power were simulated with the integrated suite of core/SOL/divertor codes JINTRAC. Various fuelling rates/locations were investigated and it was found that high values of beta, and acceptable levels of power load on the divertor outer-target, can be achieved without impurity seeding for separatrix densities above 2 × 10 19 m −3 and in conditions of partial divertor detachment. The 0D plasma parameters of the above reduced-power advanced scenario are discussed along with comparison against the reference values of the highest beta scenario in the JT-60SA research plan.